2002
DOI: 10.1103/physrevb.65.104504
|View full text |Cite
|
Sign up to set email alerts
|

Edge states and determination of pairing symmetry in superconductingSr2RuO4

Abstract: We calculate the energy dispersion of the surface Andreev states and their contribution to tunneling conductance for the order parameters with horizontal and vertical lines of nodes proposed for superconducting Sr2RuO4. For vertical lines, we find double peaks in tunneling spectra reflecting the van Hove singularities in the density of surface states originating from the turning points in their energy dispersion. For horizontal lines, we find a single cusp-like peak at zero bias, which agrees very well with th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
68
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(78 citation statements)
references
References 47 publications
10
68
0
Order By: Relevance
“…The numerical results presented here are in agreement with recent analytical calculation for the case of the low transparency barrier and triplet pairing states with horizontal lines of nodes [19]. Also only one electron band for Sr 2 RuO 4 contributes to superconductivity.…”
Section: Theory For the Tunneling Conductancesupporting
confidence: 79%
“…The numerical results presented here are in agreement with recent analytical calculation for the case of the low transparency barrier and triplet pairing states with horizontal lines of nodes [19]. Also only one electron band for Sr 2 RuO 4 contributes to superconductivity.…”
Section: Theory For the Tunneling Conductancesupporting
confidence: 79%
“…The resulting SABS has a linear dispersion as a function of k y [75,76] which is different from SABS in spin-singlet d-wave or spin-triplet p x -wave superconductor. For a ballistic junction without any roughness, it has been shown that the resulting conductance exhibits a wide variety of line shapes including broad ZBCP or dip like structure around zero voltage [77][78][79][80]. Although it is not easy to obtain reliable tunneling spectroscopy data in the abplane junction experimentally, recent fabrication of well oriented junctions enabled detection of the SABS [81].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the chiral character was not so well established experimentally (see Ref. [11] for interpretation of tunneling measurements).…”
mentioning
confidence: 99%
“…[11] and references therein). In this case, ∆ 0 should be considered a function of the electron momentum p z perpendicular to the layers: ∆ 0 → ∆ 0 cos(p z d) for triplet pairing [11] or ∆ 0 → ∆ 0 sin(p z d) for singlet pairing [10]. In both cases, averaging ∆ 2 0 (p z ) over p z generates an additional factor 1/2 in Eq.…”
mentioning
confidence: 99%